The Necessity of Convergence in Private Law - Epstein, Richard A. (2020)
This article describes the discussion between Gaius and Hume regarding the correct definition of “natural law”. It concludes that all rules that regulate man, through which he has formed not only the Civil Law of each State but also the Law of Nations, are always conventional, being the correct natural laws only those that have not had any intervention by man for their creation but exist by themselves: physics, chemistry, and biology. Once this is defined, the investigation presents the conditions under which Private Law, which regulates the daily activities of the human being and has been created gradually by the conduct of ordinary actions and without the intervention of a superior being, needs to converge with these natural laws, which are immovable, non-transferable, and invariable. The conditions will be applied to the institutions of Private Law that are part of the universal features shared by all human beings as the essence of their existence: marriage, force, property, damage, and contract.